Depressive Symptoms in Pregnancy: The Influence of Social, Psychological and Obstetric Aspects - Eleomar Vilela de Moraes; Rodolfo Nunes Campos; Mariza Martins Avelino (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Purpose To assess the prevalence of depressive symptoms and their association with social, psychological, behavioral and obstetric characteristics in pregnant women. Methods This is a cross-sectional study. The sample consisted of 375 pregnant women who attended prenatal clinics in two public maternity hospitals located in the city of Goiania, Brazil. To testify the depressive symptoms, we used the Hospital Anxiety and Depression Scale (HADS). A descriptive statistical analysis was performed using programs such as CDC EPI-INFO(tm), version 7.1.5, and Statistical Package for Social Sciences (IBM SPSS), version 21.0. Results the patients had probable depressive symptoms (15.47%) and possible depressive symptoms (25.33%). The bivariate analysis showed a significant association among "depressive symptoms" and the following variables: "single or divorced" (prevalence ratio, PR = 2.08; 95% confidence interval, CI = 1.26 to 3.44); "physical activity during pregnancy" (PR = 3.96; 95%CI = 1.28 to 12.31); exposure to "psychological/emotional" violence (PR = 4.74; 95%CI = 2.94 to 7.64); "prior mental problem" (PR = 2.66; 95%CI =1.49 to 4.73) and "obstetric complications during pregnancy" (PR = 2.53; 95%CI = 1.55 to 4.13). The multivariate analysis confirmed the association of these depressive symptoms with the variables "suffered psychological/emotional violence" (odds ratio, OR = 5.821; 95%CI = 2.939 to 11.528); "physical activity during pregnancy" (OR = 3.885; 95%CI = 1.060 to 14.231); "obstetric complications during pregnancy" (OR = 2.442; 95%CI = 1.233 to 4.834) and "single or divorced" (OR = 2.943; 95%CI = 1.326 to 6.533). Conclusions the prevalence of depressive symptoms among pregnant women is of 15.47%, and emotional violence is the main factor associated with gestational depression.